Visión grotesca de los personajes navideños de la etnia Saraguro, utilizando técnicas pictóricas mixtas - Andrade Chalan, Wilman Fabricio (2018)
The theme called "VISION GROTESCA OF THE CHRISTMAS CHARACTERS OF THE ETHNIA SARAGURO, USING MIXED PICTORIAL TECHNIQUES" will approach the theoretical and plastic study of the Christmas characters from a grotesque perception, in order to provide a cultural plastic contribution through the pictorial creation. For the effect, the deductive and inductive method was used, which allowed to deepen and analyze general characteristic aspects of other cultures and also specific as the masks and multiform attitudes of these festive characters. Through the field study registered in sketches, graphics, photographs and jointly with the plastic referents, Goya and Brueghel, it was concluded that it is necessary to question through the artistic works new considerations about the customs and traditions of this town . One believes in a necessary renovation by means of the purification of the customs.